Population structure and morphometry of Carsinoscorpius rotundicauda in Mempawah Mangrove Park, West Kalimantan - Yunita Magrima Anzani; Bambang Kurniadi; Adrian Damora (Depik, 2025)
The development of infrastructure could be one of a threat to habitat of horseshoe crabs. Regarding that, constructing of an international port at Kijing Beach in Mempawah could also become a menace to crabss habitat. Carcinoscorpius rotundicauda is known to be the most commonly found in Mempawah Mangrove Park (MMP) coastal area. This study aim is to analyze population structure and morphometry of Carsinoscorpius rotundicauda in MMP coastal area. Research was conducted on April-September 2022. Fishers collected horseshoe crab samples using trammel net. This study observed 14 characters and four ratios of morphometric, i.e. total length (TL), prosoma length (PL), opisthosoma length (OL), telson length, prosoma width (PW), carapace length (CL), compound eyes distance (CED), anal angle length (AAL), posterior angle distance (PAD), telson width (TW), median ridge length (MRL), anterior occeli length (AOL), process marginal length (PML), body weight, PL/OL, PW/PL, CL/TL, and CL/PW. The number of individuals of horseshoe crabs found high on September. The sex ratio of males to females was 1,95:1. The highest frequency relative of prosoma width was found in the range around 1214 cm (adult size). The ratio of PW/PL of female crab was significantly bigger than male. This difference could be used for determining sex of this species crabs. The growth pattern of mangrove horseshoe crabs bot males and females were negative allometry.